Gender, loyalty card membership, age, and critical incident recovery: Do they moderate experience-loyalty relationship? - Khan, I. (Elsevier Ltd, 2020)
The study examines the critical role of customer experience in determining hotel brand loyalty and the moderating role of gender, loyalty card membership, age, and critical incident recovery in this relationship. Based on a sample of 408 hotel guests and employing structural equation modeling approach, dimensions that comprise âcustomer experience with hotel brandsââhotel location, hotel staff competence, hotel stay, and ambience, hotel website and social media, and guest-to-guest experienceâare found to have relative effects on hotel brand loyalty. The results contribute to hospitality realm by suggesting the moderating effect of gender, loyalty card membership, age, and critical incident recovery on customer experience-loyalty relationship. Implications for managerial practice and theory are discussed together with limitations and further research directions. Â© 2019 Elsevier Ltd